Associations of Family Functioning and Social Support With Psychopathology in Children of Mentally Ill Parents: Multilevel Analyses From Different Rating Perspectives - Sell, Marlit; Barkmann, Claus; Adema, Bonnie; Daubmann, Anne; Kilian, Reinhold; Stiawa, Maja; Busmann, Mareike; Winter, Sibylle M.; Lambert, Martin; Wegscheider, Karl; Wiegand-Grefe, Silke (Frontiers in Psychology, 2021)
Offspring of mentally ill parents are at heightened risk for psychological symptoms. The identification of environmental factors that predict their mental health is crucial for the development of preventive and therapeutic measures. In the current study, we addressed the combined role of family functioning and social support by taking mentally ill patients’, their partners’, and children’s perspectives into account. The cross-sectional sample included n = 195 families (195 patients, 127 partners, and 295 children). Family members completed questionnaires related to family functioning, social support as well as parental and child psychopathology. We conducted multilevel analyses to investigate the associations with internalizing and externalizing problems in children. Family functioning and social support were significantly associated with child internalizing and externalizing problems. However, results varied depending on the rating perspective. We found significant interaction effects of family functioning and social support on child psychopathology. The findings point to the importance of family functioning and social support as potential targets for interventions. Findings should be replicated in future longitudinal studies.